Introduction of OSCE at Undergraduate Level - ASHRAF, M (Annals of King Edward Medical University, 2018)
To determine feasibility of introducing OSCE to assess clinical competence among final year MBBS students of King Edward Medical College in the subject of Obstetrics & Gynecology 15 stations OSCE was designed to test cognitive psychomotor and affective domains of knowledge. The OSCE was simple to organise and conduct. Students also liked it very much and demanded to introduce OSCE in other clinical subjects. OSCE is suitable for testing clinical competence of students and can identify areas where teaching methods and/or course contents are deficient.